Fatty acid composition of the edible sea cucumber Athyonidium chilensis - Careaga Quiroga, Valeria Pilar (2013)
The edible sea cucumber Athyonidium chilensis is a fishery resource of high commercial value in Chile, but no information on its lipid and fatty acid composition have been previously reported. Phospholipids were the major lipid contents of the ethanolic extracts of tubules, internal organs and body wall of A. chilensis. Saturated fatty acids predominated in tubule phospholipids (40.69%), while in internal organs and body wall phospholipids the monounsaturated fatty acids were in higher amounts (41.99% and 37.94%, respectively). The main polyunsaturated fatty acids in phospholipids were C20:2n-6, arachidonic (C20:4n-6) and eicosapentaenoic (C20:5n-3) acids. These results demonstrate for the first time that A. chilensis is a valuable food for human consumption in terms of fatty acids.